2020
DOI: 10.1177/0260106020916972
|View full text |Cite
|
Sign up to set email alerts
|

Thirst as an ingestive behavior: A brief review on physiology and assessment

Abstract: Background: Thirst is a sensation normally aroused by a lack of water and associated with a desire to drink more fluid. Aim: The aims of this brief review are twofold: (a) to summarize the thirst mechanism in how it is initiated and diminished, and (b) to describe techniques to assess human thirst accurately in a variety of situations. Discussion: Thirst is maintained via a feedback-controlled mechanism, regulated by central and peripheral factors, as well as social and psychological cues. Most studies of thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A recent review showed that the two main physiological signals for stimulation of thirst are plasma hyper‐osmolality, via cellular dehydration, and hypovolemia due to low blood volume and low arterial pressure. Also oropharyngeal and gastric distension causes activation of neural inputs in the hypothalamus, immediately suppressing the thirst sensation (Adams et al, 2020). However, whether or not this physiological mechanism is the same in dying humans is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review showed that the two main physiological signals for stimulation of thirst are plasma hyper‐osmolality, via cellular dehydration, and hypovolemia due to low blood volume and low arterial pressure. Also oropharyngeal and gastric distension causes activation of neural inputs in the hypothalamus, immediately suppressing the thirst sensation (Adams et al, 2020). However, whether or not this physiological mechanism is the same in dying humans is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Thirst is a subjective perception that motivates an animal to drink as it is a sensation aroused by a lack of water and associated with a desire to drink fluids (Adams et al 2020), which impacts animal welfare (Vanhonacker et al 2008;Tuyttens et al 2010). Providing the optimal requirements of good quality water is necessary for maintaining chicken performance and the gut health and morphology (El Sabry and Abd El-Ghany 2021;El Sabry et al, 2018a).…”
Section: Effects Of Limited Access To Water On Behavior and Welfare A...mentioning
confidence: 99%
“…5 Prolonged thirst lasting more than 24 hours can have significant negative impacts on the comfort of patients during their healing process, potentially causing fluid and electrolyte imbalances, delirium, and even post-traumatic stress disorder. 5,9,11,13,14 As such, regular assessment of thirst is crucial in order to prevent or mitigate these symptoms. 4 However, the assessment and management of thirst in intensive care patients is often neglected.…”
Section: Introductionmentioning
confidence: 99%